2019
DOI: 10.1136/bjophthalmol-2018-313760
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical analysis of the ageing tear film

Abstract: BackgroundTear film stability is important for healthy visual function, and yet little is known of the ageing mechanisms. The aim of this study was to investigate parallels between biochemical changes and clinical physical parameters, which occur in the tear film of two subject populations differing in age by over 30 years.MethodsTwo distinct age groups were chosen: 11 ‘younger’ (23.7±2.1 years) and 19 ‘older’ (63.0±4.0 years) subjects. A series of clinical tests were performed to access tear volume, tear film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A study was specifically designed to investigate the changes in tear stability and compared both biochemical and physical parameters in two cohorts separated in age by over 30 years, the older group 63.0 ± 4.0 years. A few correlations between the clinical and biochemical responses were found such as corneal staining and bulbar conjunctival redness, which coincided with elevated albumin (a biomarker for vascular permeability) and a decrease in lysozyme, lipocalin and lactoferrin proteins (the primary aqueous secretory tear proteins), which is often clinically expressed as a reduction in the tear flow rate and tear break-up time [41].…”
Section: Dry Eyementioning
confidence: 99%
“…A study was specifically designed to investigate the changes in tear stability and compared both biochemical and physical parameters in two cohorts separated in age by over 30 years, the older group 63.0 ± 4.0 years. A few correlations between the clinical and biochemical responses were found such as corneal staining and bulbar conjunctival redness, which coincided with elevated albumin (a biomarker for vascular permeability) and a decrease in lysozyme, lipocalin and lactoferrin proteins (the primary aqueous secretory tear proteins), which is often clinically expressed as a reduction in the tear flow rate and tear break-up time [41].…”
Section: Dry Eyementioning
confidence: 99%
“…A recent meta-analysis suggested LACTO level in tears is a good candidate as dry eye syndrome diagnostic biomarker [48]. The plasma-derived proteins ALB and TRANSF can be considered as indirect sign of subclinical inflammation as it occurs when there is an increase of protein leakage from inflamed conjunctival vessels [49][50][51]. They are usually present in a negligible amount in tears of normal subjects [26], and it has been shown that ALB increases whereas TRANSF decreases in moderate DED [27]; it is not clear why these proteins behave contrarily and if this may be due to blood-epithelial barrier functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Results were displayed as gel-like image bands or as electropherogram peaks for each sample. Peaks in the protein profile were identified based on their molecular weight or mass (kDa) and the findings from previous studies, 4,5,7,12–15 and concentrations were obtained from the result page of the software.…”
Section: Methodsmentioning
confidence: 99%